THE SYSTEMATIZATION OF CLASSES ABOUT BIOMECHANICAL CONTENTS IN THE CONTEXT OF THE SCHOLASTIC PHYSICAL EDUCATION (Fiep Bulletin - online, 2015)
This study presents a pedagogic sequence to the work with the theme 'speed' to the third grade of Fundamental Education , on biomechanical perspective. It is about an experience based on historical-critical pedagogic proposal and also on the systematization of the contents of the Physical Education curricular component. This experience has as main objective to verify the possibility of working this theme with this age group and observe which relations come from practical-reflexive experiences. The results have shown the students' difficulty in facing theoretical themes in Physical Education classes, fruit of a practical experience in this area. They have also shown that planned and structured actions may break paradigms and broadens the Physical Education pedagogical horizons on the educational section.
Keywords: Scholastic Physical Education; Teaching Methodology; Physical Education.